Improving the availability of prescription drugs in Lebanon: a critical analysis of alternative policy options - Amena El-Harakeh; Sean J. Haley (BMC, 2022)
Abstract The economic downfall in Lebanon and the destruction of the Beirut Port have had a crippling effect on all players in the health sector, including hospitals, healthcare providers, and the pharmaceutical and medical supply industry. The outbreak of COVID-19 has further aggravated the crisis. To address the challenges facing the pharmaceutical industry, Lebanon must create a stable and secure source of prescription drug production. Two alternative approaches are presented to address the crisis: (1) amending the subsidy system and supporting local pharmaceutical production, and (2) promoting the prescription and use of generic drugs. Investing in local production is promising and can lead to establishing trust in the quality of drugs produced locally. These efforts can be complemented by promoting the prescription and use of generic drugs at a later stage, after having had established a well-operating system for local drug production.